Numerical investigation of inclined plate anchors in clay with linearly increasing undrained shear strength. (15th September 2021) - Cheng, Xinglei; Jiang, Ziqiang; Zhang, Jianxin; Wang, Piguang; Zhao, Yanbing
Abstract: Plate anchors have been increasingly used to provide a mooring system for offshore floating facilities due to their relatively high efficiency and low costs. The analysis of anchor behaviour can be usually divided into two categories "immediate breakaway" and "no breakaway", which correspond to the "vented anchors" and "attached anchors". Most of the previous literatures focus on these two extreme cases: vented anchors in clays without weight and attached anchors. However, the vented anchors in clays with weight, as a most common state, are in the intermediate state of the two extreme cases. At the cases, the change law of the pullout capacity of plate anchors with embedment depth, inclination angles and overburden pressure is relatively complex and needs further study. This paper investigates the pullout behaviour of inclined strip plate anchors in clays with linearly increasing shear strength by performing a series of finite element analysis, and clarify the change law of the pullout capacity and the failure mechanism of plate anchor in the intermediate state. Two new formulas are proposed to predict the pullout factor for inclined vented and attached anchors. Related research results can provide a reference for the engineering design of inclined plate anchors in undrained clay. Highlights: The pullout behaviour of inclined plate anchors in normally consolidated clay is simulated. The coupling effect of inclination angles and many other factors on the pullout capacity is investigated. The effects of soil weight and anchor-soil interface conditions on the failure mechanism are revealed. New empirical formulas are proposed to predict the pullout capacity factor for vented and attached anchors.